Implementasi Corporate Social Responsibility (CSR) Pada Lembaga Keuangan Syariah (Studi Kasus Pada BRI Syariah Tahun 2014-2015) - Muhammad Tho'in (Al-Tijary, 2017)
The concept of Corporate Social Responsibility shows that companies not only oriented to the quest for profit, but also obliged to maintain harmony and harmony with the stakeholders. CSR is ultimately to improve living conditions and benefits the company itself, the surrounding community, and the general public. Various CSR consists of economic responsibility, legal responsibility, ethical responsibility, and the responsibility of generosity.The purpose of this study was to determine how the implementation of Corporate Social Responsibility by BRI Syariah in 2014 and 2015 also the field of what is priority activity. The research method used quantitative descriptive data sources in the form of secondary data from the financial statements of BRI Syariah in 2014 and 2015. The results showed that the implementation in 2014 of CSR activities by BRI Syariah had been performed on six fields with total realization of Rp.2.714.278.584. While in 2015 BRI Syariah CSR activities had been conducted in 5 fields with total realization of Rp.1.374.468.181. Priority areas of CSR activities during 2014 and 2015 by BRI Syariah changes. This is because of the program Syariah BRI CSR was conducted in accordance with the situation and conditions in the field, although previously had been mapped. For 2014, CSR priority program for donations, calamities and natural disasters which amount of Rp.1.279.788.110 or 47% of the total realization of CSR in 2014. While in 2015 CSR priority program to help proselytizing and religious facilities in the amount of Rp.598.203 .000 or 44% of the total realization of CSR in 2015.